2017
DOI: 10.1589/jpts.29.536
|View full text |Cite
|
Sign up to set email alerts
|

The effects of extracorporeal shock wave therapy on the pain and function of patients with degenerative knee arthritis

Abstract: [Purpose] The purpose of this study was to identify the effects of extracorporeal shock wave therapy on the pain and function of patients with degenerative knee arthritis. [Subjects and Methods] Twenty patients with degenerative knee arthritis were divided into a conservative physical therapy group (n=10) and an extracorporeal shock wave therapy group (n=10). Both groups received general conservative physical therapy, and the extracorporeal shock wave therapy was additionally treated with extracorporeal shock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…[23]. The present study also showed statistically significant decrease in the pain intensity level and improvement in PPT of the trigger points in both groups but more improvement in shock wave therapy group, This result may be because the explanation of Ji-Hyun Lee et al(2017) that shock waves are a sort of sound waves that can be transmitted through soft tissues without loss of energy, and their fine and repetitive stimulations are effective for reducing pain. In addition, stimulations caused by shock waves form new muscular fibers by facilitating the secretion of substances that generate blood vessels around an affected region.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…[23]. The present study also showed statistically significant decrease in the pain intensity level and improvement in PPT of the trigger points in both groups but more improvement in shock wave therapy group, This result may be because the explanation of Ji-Hyun Lee et al(2017) that shock waves are a sort of sound waves that can be transmitted through soft tissues without loss of energy, and their fine and repetitive stimulations are effective for reducing pain. In addition, stimulations caused by shock waves form new muscular fibers by facilitating the secretion of substances that generate blood vessels around an affected region.…”
Section: Discussionsupporting
confidence: 68%
“…These new muscular fibers increase blood flow around a lesion and induce the reformation of blood vessels, which eventually stimulates and reactivates the healing process of the tendons and the tissues around them, thereby stabilizing the tissues. The secretion of substances induces lymphangiogenesis through upregulation of expression of vascular endothelial growth factor and basic fibroblast growth factor [24]. Plaisier PW et al(1994) provided other hypothesized mechanisms of action include the physical alteration of small axons, thereby inhibiting pain impulse conduction; chemical alteration of pain receptor neurotransmitter, thereby preventing pain perception; and hyperstimulation activation of the gate control mechanism, thereby affecting analgesia [25].…”
Section: Discussionmentioning
confidence: 99%
“…The sample size ranged from 18 to 160. All experimental groups received ESWT, while control groups received different treatments including placebo [22,23,25,26,28,30,34,48,49,51,52], medication [31,32,43,44,50], intra-articular injections [21,26,27,29,35,36,39,40], traditional Chinese medicine [38,41,42,45,2 BioMed Research International 46], ultrasound [22,24,47], surgery [33], and kinesiotherapy (KIN) [37].…”
Section: Statisticalmentioning
confidence: 99%
“…According to the recommendation of WHO, the patients with BMI ≥25 Kg/m 2 were defined as overweight, and the patients with BMI ≥30 Kg/m 2 were defined as obese [4]. ere are many conservative treatments for OA, such as drug therapy, intra-articular injection of HA and PRP [5], physical therapy [6], and ozone therapy [7]. All kinds of treatments aim at relieving knee pain and improving joint mobility [8].…”
Section: Introductionmentioning
confidence: 99%